2005
DOI: 10.1021/jf048270e
|View full text |Cite
|
Sign up to set email alerts
|

Potato Peel Extracta Natural Antioxidant for Retarding Lipid Peroxidation in Radiation Processed Lamb Meat

Abstract: The effective utilization of potato peel, a waste generated in large quantities by the food industry, as an antioxidant was investigated. Potato peel extract (PPE) exhibited high phenolic content (70.82 mg of catechin equivalent/100 g), chlorogenic acid (27.56 mg/100 g of sample) being the major component. The yield of total phenolics and chlorogenic acid increased by 26 and 60%, respectively, when the extract was prepared from gamma irradiated (150 Gy) potatoes. PPE showed excellent antioxidant activity as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 37 publications
2
85
1
4
Order By: Relevance
“…Results suggested that ethanol extracts of potato peel can be employed as natural antioxidant to prevent lipid and protein. Kanatt et al (2005) used potato peel waste as a source of natural antioxidants and test its effectiveness in reducing lipid peroxidation of radiation-processed meat. Radiation processing is one of the most effective technologies for sterilization in raw meat and meat products.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Results suggested that ethanol extracts of potato peel can be employed as natural antioxidant to prevent lipid and protein. Kanatt et al (2005) used potato peel waste as a source of natural antioxidants and test its effectiveness in reducing lipid peroxidation of radiation-processed meat. Radiation processing is one of the most effective technologies for sterilization in raw meat and meat products.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The peel removed from the potato tuber prior to slicing and frying is a principal byproduct in typical potato chips, and a substandard portion of mashed potato is further loaded in fabricated potato. Potato peel has a high content of phenolic compounds, to which antioxidant activity is attributed (Kanatt et al, 2005;De Sotillo et al, 1994). The main components were identified as chlorogenic acid and caffeic acid in free-form phenolics (Kanatt et al, 2005) and ferulic acid in bound-form phenolics (Nara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Potato peel has a high content of phenolic compounds, to which antioxidant activity is attributed (Kanatt et al, 2005;De Sotillo et al, 1994). The main components were identified as chlorogenic acid and caffeic acid in free-form phenolics (Kanatt et al, 2005) and ferulic acid in bound-form phenolics (Nara et al, 2006). Potato peel extract can be used as a natural antioxidant in soy bean oil (Rehman et al, 2004) and has been shown to retard lipid oxidation in radiation-processed lamb meat (Kanatt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potato peel contains many phenolic compounds, some in free form and some bound. The largest portion consists of Cholorogenic acid (CGA), a derivative of caffeic acid (CFA) and Quinic acid (QNA) [30,31]. Singh et al [32] demonstrated that the aqueous extract of potato peel contains a number of antioxidant compounds viz., chlorogenic acid, gallic acid, caffeic acid which can effectively scavenge various reactive oxygen species/free radicals under in vitro conditions and attributed the broad range of antioxidant activity of peel extracts to multiple mechanism.…”
Section: Potatomentioning
confidence: 99%